Medioitunut valta ja politiikan paluu Kyselytutkimus suomalaispäättäjien suhteesta mediaan 2009 ja 2019 - Reunanen, Esa (Tampere University Press, 2021)
This book [Mediatized power and the return of the political] describes Finnish decision-makers' relationship with the media. It is based on surveys in 2009 and 2019. In 2009 there were 419 and in 2019 484 respondents, all of them having an influential position in some of the eight societal sectors covered in the study. The results show a moderate change from a consensus-oriented and networking decision-making culture towards a more ideologic and power-based way of negotiating. However, it seems that this has not affected how open or transparent the negotiation-processes are or how prone the decision-makers are to leak confidential information. The decision-makers' relationship with media publicity has become more professional and strategic. The results point to an increased role of social media in communications management while the role of the news media seems to be diminishing. Even though the decision-makers view publicity as an even more risky and strategic arena of political struggle than they did before, they also seem now acknowledge more clearly the rational aspects of journalism. The self-reported role of media publicity as a source of personal authority has somewhat diminished while there seems to be no change in how prone the decision-makers think they are for the impacts of media publicity.